Traumatic experiences and posttraumatic stress disorder in Spanish university students - Bados, Arturo; Greco, Antonella; Toribio, Lidia (Anales de Psicología / Annals of Psychology, 2012)
The aim of this study was to analyze in college students the occurrence of different traumatic events, as well as the conditional risk and current prevalence of probable posttraumatic stress disorder (PTSD). Four hundred and thirty two college students completed a questionnaire concerning traumatic experiences, as well as a scale of PTSD. Of the sample, 60.6% had experienced a traumatic event. The most common was the violent or unexpected death of loved ones. The death of loved ones and suffering from physical or sexual violence were the worst events. The conditional risk of probable PTSD was 8.6% and the current prevalence, 5.2%. These data are probably an overestimate of the true values, probably due to having used questionnaires rather than a structured interview, but indicate that although the experience of traumatic events is common, the vast majority of people exposed to these events overcome them.